2016
DOI: 10.3390/nu8110651
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Intake of Pregnant and Breastfeeding Women in Indonesia: A Cross-Sectional Survey with a Seven-Day Fluid Specific Record

Abstract: During pregnancy and lactation, the adequate intake (AI) for total water intake is increased. This cross-sectional survey aimed to assess Total Fluid Intake (TFI; sum of drinking water and all other fluids) of 300 pregnant and 300 breastfeeding women in Indonesia. A seven-day fluid specific record was used to assess TFI. Mean TFI of pregnant and breastfeeding women were 2332 ± 746 mL/day and 2525 ± 843 mL/day, respectively. No significant difference in TFI between pregnancy trimesters was observed, while TFI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 25 publications
1
26
0
3
Order By: Relevance
“…Though the fluid intake data collected in this study are declarative, they are consistent with surveys that have shown that pregnant and breastfeeding women across the world do not meet the daily AWI [4,16] . The overall positive reactions of women in our study, in regards to the simplicity and utility of Tool 2, suggest that a UC scale-based tool could be utilized by healthcare professionals to help pregnant and breastfeeding women selfassess their hydration.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Though the fluid intake data collected in this study are declarative, they are consistent with surveys that have shown that pregnant and breastfeeding women across the world do not meet the daily AWI [4,16] . The overall positive reactions of women in our study, in regards to the simplicity and utility of Tool 2, suggest that a UC scale-based tool could be utilized by healthcare professionals to help pregnant and breastfeeding women selfassess their hydration.…”
Section: Discussionsupporting
confidence: 79%
“…In one study conducted with 308 pregnant or breastfeeding women in Mexico, 41% of pregnant women and 54% of breastfeeding women failed to meet national intake guidelines [4] . An Indonesian survey reported nearly identical results among 595 pregnant or breastfeeding women: 42% of pregnant women and 54% of breastfeeding women consumed less than the AI of water from fluids, established by the Indonesian Ministry of Health [5] . Finally, a recent observational study that followed a sample of American women, from the first trimester of pregnancy into early breastfeeding, reported mean total fluid intake levels of 2.3 and 2.1 L·day -1 , respectively, which indicated that the women did not increase their water intake at all during the early weeks of breastfeeding [6].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The study was approved on December 23, 2013, by the Ethics Committee of the Faculty of Medicine Universitas Indonesia (number 783/H2.F1/ ETIK/2012). Full protocol details with the inclusion and exclusion criteria have been described elsewhere [7] . Additionally, this survey followed the same sampling method, protocol and method for fluid assessment as those performed in the Liq.In 7 surveys [8,9] .…”
Section: Methodsmentioning
confidence: 99%
“…24 In addition, higher water intake rates were observed in pregnant and lactating women compared to control women, as weight gain during pregnancy and milk output during lactation require more water physiologically, contributing to prenatal exposure and impacting fetal development. 19,25 Subsequently, humans are potentially exposed to EDCs daily, and there are possible health risks associated with drinking water intake.…”
Section: Human Exposure To Edcs In Drinking Watermentioning
confidence: 99%